Studies on the genus Aporcelaimellus Heyns, 1965 (Nematoda, Dorylaimida, Aporcelaimidae). Four atypical species with simple uterus from Southern Iberian Peninsula - Álvarez-Ortega, Sergio; Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2013)
Three new and one known species of the genus Aporcelaimellus, collected mainly in natural areas from the Iberian Peninsula and characterized by having a simple uterus and atypical caudal region are described and illustrated, including line drawings, LM pictures and/or SEM pictures. Aporcelaimellus deserticola sp. n. is distinguished by its body 1.79–2.43 mm long, lip region 14–16 μm broad and offset by expansion rather than by constriction, odontostyle 18–21 μm long, neck 464–555 μm long, pharyngeal expansion 234–283 μm long or 49–52% of total neck length, a dorsal cell mass present at level of anterior end of intestine, uterus 34–67 μm long or 0.6–1.1 times the corresponding body diameter, V = 49–55, tail conical with rounded terminus (29–43 μm, c = 47–66, c’ = 0.9–1.4) and bearing a short but perceptible hyaline portion, and male unknown. Aporcelaimellus hyalinus sp. n. is characterized by its body 1.49–2.23 mm long, lip region offset by constriction and 13–16 μm broad, odontostyle 14–16 μm long, neck 389–474 μm long, pharyngeal expansion 183–242 μm long or 45–53% of total neck length, uterus 44–106 μm long or 0.7–1.8 times the corresponding body diameter, V = 48–55, tail conical with rounded terminus (27–41 μm, c = 38–68, c’ = 1.0–1.4) and short inner core, spicules 56 μm long, and seven irregularly spaced ventromedian supplements. Aporcelaimellus rarus sp. n. is distinguished by its body 1.96–2.34 mm long, lip region offset by constriction and 14–16 μm broad, odontostyle 15–16 μm long, neck 411–518 μm long, pharyngeal expansion 196–270 μm long or 48–52% of total neck length, a dorsal cellular mass at a short distance behind the cardia, uterus 63–96 μm long or 0.8–1.5 times the corresponding body diameter, V = 51–56, female tail short and conical (28–40 μm, c = 50–74, c’ = 0.7–0.9) with rounded terminus and bearing a dorsal concavity at its posterior half, and males unknown. New data are provided for A. salicinus. A discussion of these atypical species is also provided.